Perbandingan Anestesi Epidural dengan Subarachnoid Block terhadap Kualitas Pemulihan Pasien Bedah Ortopedi: Systematic Literature Review - Adista Veradina; Made Suandika; Tophan Heri Wibowo (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Fractures and orthopedic surgeries are common procedures that require optimal regional anesthesia techniques to support patient recovery. This study aims to compare the effectiveness of epidural anesthesia and subarachnoid block (SAB) on the quality of recovery in orthopedic surgery patients through a systematic literature review. The literature search was conducted in the PubMed, ScienceDirect, and Google Scholar databases for the period 2015–2025, using the PRISMA guidelines. A total of 6 studies that met the inclusion criteria were analyzed narratively. The results indicate that epidural techniques and spinal-epidural combinations such as CSEA, CSA, and SCSE tend to yield better recovery outcomes compared to SAB, particularly regarding hemodynamic stability, duration of analgesia, postoperative pain control, and early mobilization. Additionally, the incidence of hypotension, urinary retention, and back pain is lower with epidural or combination techniques. However, SAB remains superior in terms of rapid onset of action and ease of technique. In conclusion, epidural techniques better support multidimensional recovery quality in orthopedic patients compared to SAB.